Corticosterone induces obesity partly via promoting intestinal cell proliferation and survival - Wang, Guanhao; Li, Shuanqing; Li, Yingqi; Zhang, Meihui; Xu, Ting; Li, Tianming; Cao, Lining; Lu, Jianfeng (Frontiers in Endocrinology, 2023)
A vicious cycle ensues whereby prolonged exposure to social stress causes increased production of glucocorticoids, leading to obesity even further. Understanding the role of glucocorticoids, the key element in the vicious circle, might be helpful to break the vicious circle. However, the mechanism by which glucocorticoids induce obesity remains elusive. Herein we find that administration of corticosterone (CORT) to mice promotes the proliferation and survival of intestinal cells, which might contribute to the longer small intestines and the elongated intestinal villi, thus leading to increased nutrient absorption and obesity in mice. RNA-seq was performed to analyze transcriptional alterations in small intestines and livers after CORT-treatment, indicating differentially expressed genes (DEGs) were enriched in several cell growth/death-associated signaling pathways. This study would provide novel therapeutic clues for stress or glucocorticoids-related obesity.